Genetically engineered crops for sustainably enhanced food production systems - Abdul Aziz, Mughair; Brini, Faical; Rouached, Hatem; Masmoudi, Khaled (Frontiers in Plant Science, 2022)
Genetic modification of crops has substantially focused on improving traits for desirable outcomes. It has resulted in the development of crops with enhanced yields, quality, and tolerance to biotic and abiotic stresses. With the advent of introducing favorable traits into crops, biotechnology has created a pathway for the involvement of genetically modified (GM) crops into sustainable food production systems. Although these plants heralded a new era of crop production, their widespread adoption faces diverse complexities due to concerns about the environment, human health, and moral issues. Mitigating these concerns with scientific investigations is vital. Hence, the purpose of the present review is to discuss the deployment of GM crops and their effects on sustainable food production systems. It provides a comprehensive overview of the cultivation of GM crops and the issues preventing their widespread adoption, with appropriate strategies to overcome them. This review also presents recent tools for genome editing, with a special focus on the CRISPR/Cas9 platform. An outline of CRSIPR/Cas9 developed crops role in achieving sustainable development goals (SDGs) by 2030 is detailed. Some perspectives on the approval of GM crops are also laid out for the new age of sustainability. The advancement in molecular tools through plant genome editing addresses many of the GM crop issues and facilitates their development without any foreign genes. It will allow for a higher acceptance rate of GM crops in sustainable agriculture with rapid approval for commercialization. The current genetic modification of crops forecasts to increase productivity and prosperity in sustainable agricultural practices. The right use of GM crops has the potential to inflict more benefit than harm, with its ability to alleviate food crises around the world.